Public sanitation interventions and household clean energy adoption: Evidence from China’s renovating water supply and toilets - Ping Wang; Lijiao Liu (PLoS ONE, 2025)
By 2021, approximately 2.3 billion people worldwide still relied on polluting fuels and technologies for cooking. Such harmful fuels pose serious risks to both health and the environment, contributing to health issues and constraining economic activities. Based on the China Health and Retirement Longitudinal Study data, this study investigates whether and how the renovation of tap water and sanitary toilets affects clean energy adoption among rural households in China by utilizing a Probit model. The results demonstrates that the probability of rural households using clean energy for cooking significantly increased by 8.0 percentage points after undergoing the renovation of tap water and sanitary toilets. These effects are particularly pronounced in households with male heads and low-income households. Mechanism analysis suggests that the renovation of tap water and sanitary toilets significantly elevates educational levels, strengthens cognitive abilities, and fosters the accumulation of human capital, while also raising environmental awareness, thereby driving the utilization of clean energy sources. These findings underscore the significance of sanitation improvements in driving energy transition in rural areas of China. For policymakers focusing on sanitation facilities and socioeconomic development in developing countries, such as China, investments in sanitation infrastructure can yield broad benefits beyond public health, fostering human capital accumulation, environmental awareness, and energy transition. These outcomes have significant implications for long-term sustainable development goals.